Quran-based spiritual psychotherapy: insights from Islamic scholarship and modern psychology on obsessive-compulsive disorder (was-was) - Faiz Hadi Sanadi,; Mazlan Ibrahim,; Noraziah Mohamad Zin,; Arif Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Obsessive-Compulsive Disorder (was-was) are psychological and spiritual concerns necessitating a comprehensive treatment strategy to alleviate obsessive, compulsive symptoms and emotional turmoil. This study seeks to evaluate the efficacy of Quran-based spiritual psychotherapy, incorporating components of zikr, prayers and tazkiyah (self-purification), in assisting Muslim patients in stress management and emotional equilibrium enhancement. The discussion concurrently addresses the incorporation of contemporary methodologies, such Cognitive Behavioral Therapy (CBT) and Exposure and Response Prevention (ERP), to assess the compatibility of treatment with the cultural and religious beliefs of patients. A qualitative methodology was utilized by analyzing holy scriptures, contemporary literature, and perspectives from distinguished Islamic academics. The results demonstrate that the amalgamation of spiritual and contemporary therapy is successful in alleviating OCD symptoms and fortifies faith as a safeguard against spiritual disruptions. This study emphasizes that this comprehensive treatment paradigm provides an appropriate option for the Muslim population in tackling intricate mental health issues.